PREVALENCE OF INTESTINAL PARASITIC INFESTATIONS IN PATIENTS ATTENDING A TERTIARY CARE HOSPITAL OF CENTRAL INDIA - Gupta, Abha; Saraswat, Ashish; Mehta, Abhishek (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to find out the prevalence and spectrum of intestinal parasitic infestations among the patients attending the associated hospital with complaints of abdominal pain and diarrhea. Methods: A total of 117 stool samples were collected and screened for intestinal parasitic infection. Plastic containers with identification numbers were given to the patients, and information regarding name, age, sex, ward, and findings of stool routine microscopy were recorded. All samples were examined macroscopically for appearance, color, and the presence of blood and mucus then analyzed using direct microscopy for the presence of intestinal parasites. Results: It was found that intestinal parasitic infections were mainly attributed to Entamoeba histolytica, Ascaris lumbricoides, and Giardia lamblia which are pretty prevalent in the region of the study. Conclusion: It was found that intestinal parasitic infections were mainly attributed to E. histolytica, A. lumbricoides, and G. lamblia which are pretty prevalent in the region of the study.